META ANALISIS PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL BERBASIS DIGITAL TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Syafa Buana; Anggi Citra Apriliana, Herlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the effect of digital-based audio-visual media on elementary students’ reading comprehension skills through a qualitative meta analysis approach. The background of this study stems from the persistent issue of low reading comprehension among Indonesian students, as reflected in national and international assessments. The research employs a thematic synthesis model adapted from Miles and Huberman's interactive analysis approach. A total of 20 SINTA-indexed journal articles published between 2021–2025 were selected through purposive sampling. Data were analyzed based on reading comprehension types (literal, interpretative, critical, and creative), subject content, digital audio visual media types, and the research results. The findings show that most studies report positive impacts of digital audio-visual media in improving students' reading comprehension. The dominant levels found were literal and interpretative, with some studies also highlighting critical and creative comprehension. Various media formats such as interactive videos, digital comics, E-bigbook, Literacy Cloud, Edpuzzle, and Flipbook were effectively used. The research concludes that digital based audio-visual media serve not only to support reading comprehension skills but also foster motivation, creativity, and digital literacy among elementary school students.